FEELING THE RHYTHMS OF CODE - Saariketo, Minna (AoIR Selected Papers of Internet Research, 2018)
This presentation examines how the softwarization of everyday life is experienced. The point of embarkation is the observation that despite the proliferation computation in the everyday, people pay little attention to the conditions of software and its role in shaping their mundane time-spaces. I will discuss results from a case study that used Henri Lefebvre’s rhythmanalysis (1992/2004) to shed light on how the rhythms of code-based technology are experienced. The research design of the intervention was inspired by the idea of privacy mirrors (Ngueyn and Mynatt 2002). Research participants (n=13), who described their relation to their devices as intense, used tracking software (RescueTime, ManicTime, App Usage or RealizD) in their ICTs and kept media diaries. These were used as artefacts in the interviews to enable reflection on the role of ICTs in daily life. The results from the rhythmanalysis show how the complex intertwinement of digital devices and applications in the everyday evokes manifold feelings. Simultaneously, technology is perceived as an aid in organizing and managing the daily life, but it also induces feelings of losing control, chaos, and burden. The results suggest that although people might take for granted the infrastructural conditions of technology, such as data mining, they still actively negotiate their relation to devices and applications vis-à-vis temporality. Outcomes from the intervention encourage developing further research designs that use the means of softwarization itself (e.g. tracking and digital traces) to enable critical reflection.